Rheumatic heart disease echocardiographic screening: approaching practical and affordable solutions. Issue 9 (18th February 2016) - Nascimento, Bruno R; Nunes, Maria Carmo P; Lopes, Eduardo L V; Rezende, Vitória M L R; Landay, Taylor; Ribeiro, Antonio L P; Sable, Craig; Beaton, Andrea Z
Abstract : Rheumatic heart disease (RHD) affects at least 32.9 million people worldwide and ranks as a leading cause of death and disability in low-income and middle-income countries (LMICs). Echocardiographic screening has been demonstrated to be a powerful tool for early RHD detection, and holds potential for global RHD control. However, national screening programmes have not emerged. Major barriers to implementation include the lack of human and financial resources in LMICs. Here, we focus on recent research advances that could make echocardiographic screening more practical and affordable, including handheld echocardiography devices, simplified screening protocols and task shifting of echocardiographic screening to non-experts. Additionally, we highlight some important remaining questions before echocardiographic screening can be widely recommended, including demonstration of cost-effectiveness, assessment of the impact of screening on children and communities, and determining the importance of latent RHD. While a single strategy for echocardiographic screening in all high-prevalence areas is unlikely, we believe recent advancements are bringing the public health community closer to developing sustainable programmes for echocardiographic screening.